Pengaruh Model Problem Based Learning (PBL) Berbasis Canva pada Mata Pelajaran Ipas Terhadap Hasil Belajar Peserta Didik Kelas IV SD Negeri 05 Padang Pasir - Amanda, Shelvia; Astimar, Nelly (Indo-MathEdu Intellectuals Journal, 2025)
The aim of this research is to determine the effect of the Problem-Based Learning model on the learning outcomes of pattern imagery and number patterns in the fourth grade of SD Negeri 05 Padang Pasir, Padang City, for the 2024/2025 academic year. The type of research in this study is Quasi Experimental Design, which falls under the Nonequivalent Control Group Design category. The population in this study consists of all students in the fourth grade of SD Negeri 05 Padang Pasir, Padang City, totaling 59 individuals. Sampling technique is a non-probability sampling type of purposive sampling obtained from class IV A as the experimental class and class IV C as the control class. The research instrument is an objective test in the form of multiple-choice questions. Based on the analysis of the research data that has been conducted, the average pretest score of the experimental class is 58.39 and that of the control class is 56.42. After treatment was given to the experimental class using the Problem Based Learning model and the control class using the Direct Learning model, the average posttest score of the experimental class was 83.47 and that of the control class was 66.68. The analysis of the data from the hypothesis test conducted showed that t hitung was 3.83 and t tabel was 1.68. This means that t hitung > t tabel, that is 3.83 > 1.68, so the hypothesis H1 is accepted and H0 is rejected, which indicates that there is an effect of the Canva-based Problem Based Learning model on the Learning Outcomes of the States of Matter in Class IV of SD Negeri 05 Padang Pasir, Padang City.